Knowledge of Iodine Deficiency Disorders and Intake of Iodized Salt in Residents of Mekelle Tigray, Ethiopia - Teklit Gebregiorgis Ambaye (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2015)
When we see about the awareness of the people in the world it is low due to that the peoples are suffered from goiter disease and other problems related to iodized and this problem are also faced in our country especially in Tigray Mekelle city. Despite numerous educational programmers to create awareness about iodized salt and iodine deficiency disorders (IDD), a survey conducted in the in Mekelle in 2012 revealed that the goiter rate stood at 18.8%; and 78.1% of households consumed iodized salt, which is below the goal of the IDD programme in Ethiopia which aimed at 90% household consumption of iodized salt by the end of 2015 and sustaining the gains by 2012. It was therefore, considered timely to investigate the knowledge levels and the extent of utilization of iodized salt among the people living in Mekelle, and with the lowest intake (76.4%) of iodized salt based on findings of the 2012 survey. This was a descriptive cross-sectional study. It was conducted among a total of 280 household members, mainly in charge of meal preparation, who were interviewed using a structured interview guide. A combination of cluster and simple random sampling techniques was used to select the respondents from all the respondents' The study revealed that 75.6% of households in the district consumed iodized salt (including households described as occasional users of iodized salt), and knowledge of iodized salt was quite high, as 72% of the respondents knew that not every salt contained iodine. In addition, 69.3% indicated that an inadequate intake of iodized salt can lead to the development of goiter. Despite the high awareness level, only 64.6% of respondents indicated that they exclusively used iodized salt for cooking. The main reason given by exclusive users of common salt was that the price of iodized salt is a little higher than that of common salt. Although majority of the respondents are aware of the importance of iodized salt and iodine deficiency disorders, only 64.6% exclusively used iodized salt, suggesting that respondents' high knowledge levels did not necessarily translate into an increase in the number of households who used iodized salt. Existing laws and policies on universal salt iodization and quality assurance of iodized salt from the production stage to the distribution/selling stage should be enforced.